Uwarunkowania i perspektywy rozwoju strategii masowej indywidualizacji w Polsce - Piotrowski, Maciej (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The paper discusses mass customization and personalization strategy (MCP) which, according to some experts, will help to maintain the competitive position of European companies. Due to first implementations of this strategy in EU countries, it is legitimate to study the opportunities for the development in Polish business environment. The paper outlines the research plan and its first results, the key element of the PhD thesis being prepared by the author. The practical results will include a guidebook for entrepreneurs describing the industries, in case of which the introduction of MCP is possible and reasonable as well as necessary steps to be undertaken. The emphasis will be laid on the proper use of IT and production infrastructure as main enablers of MCP. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1086, s. 206-212